2010
DOI: 10.1104/pp.109.151829
|View full text |Cite
|
Sign up to set email alerts
|

Nonhost Resistance of Barley to Different Fungal Pathogens Is Associated with Largely Distinct, Quantitative Transcriptional Responses    

Abstract: Nonhost resistance protects plants against attack by the vast majority of potential pathogens, including phytopathogenic fungi. Despite its high biological importance, the molecular architecture of nonhost resistance has remained largely unexplored. Here, we describe the transcriptional responses of one particular genotype of barley (Hordeum vulgare subsp. vulgare 'Ingrid') to three different pairs of adapted (host) and nonadapted (nonhost) isolates of fungal pathogens, which belong to the genera Blumeria (pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 55 publications
(65 reference statements)
4
78
0
Order By: Relevance
“…For example, hypersensitive response (HR) is a typical resistance phenomenon that is associated with both R-gene and some nonhost resistance. Similar global gene expression profiles (Tao et al, 2003) and other induced responses (Zimmerli et al, 2004;Aghnoum and Niks, 2010;Zellerhoff et al, 2010;Hiruma et al, 2011) have been observed during nonhost resistance against fungal and bacterial pathogens.…”
mentioning
confidence: 50%
“…For example, hypersensitive response (HR) is a typical resistance phenomenon that is associated with both R-gene and some nonhost resistance. Similar global gene expression profiles (Tao et al, 2003) and other induced responses (Zimmerli et al, 2004;Aghnoum and Niks, 2010;Zellerhoff et al, 2010;Hiruma et al, 2011) have been observed during nonhost resistance against fungal and bacterial pathogens.…”
mentioning
confidence: 50%
“…and analyzed using the barleyPGRC1 macroarray at IPK Gatersleben. 4 As a result 250 genes could be identified, which were either up or downregulated during the nonhost interaction. Expression level of 180 of these genes was not altered during the host interaction.…”
Section: Mlo-silencing As a Case Studymentioning
confidence: 99%
“…10 Among the genes that were specifically upregulated in the Magnaporthe nonhost interaction and therefore might play a crucial role in NHR, several lipid transfer proteins, a cytochrome P450 and an ascorbate peroxidase were listed. 4 Functional characterization of these genes could be achieved by generating stable RNAi transformants, however, this is difficult and time-consuming in barley. To circumvent this drawback we decided to adopt a VIGS approach using the rod-shaped hordeivirus BSMV as a vector which was the first to be used among monocotyledonous plants.…”
Section: Mlo-silencing As a Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: sasanuma@tds1.tr.yamagata-u. ac.jp induced or repressed by infection with other pathogens, such as rust and blast, suggesting that the powdery mildew resistance induced by the Mlo genes is part of a complex response to various pathogens (Zellerhoff et al, 2010). The expression of Mlo was also increased during leaf senescence, by wounding, and by Paraquat treatment ( (Piffanelli et al, 2002).…”
Section: Introductionmentioning
confidence: 98%